EFFECT OF SUPPLEMENTATION OF PROBIOTICS AND MULTIENZYMES IN LOW PROTEIN DIET ON THE PERFORMANCE OF JAPANESE QUAILS - Rathi, A D; Kukde, R J; Ramteke, B N; Lanjewar, R D; Patankar , R B (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
An experiment was conducted to study the effect of probiotics and multienzymes in low protein diet of Japanese quails. One hundred sixty quail chicks were uniformly distributed into four groups viz. T0, T1, T2 and T3. Group T2 was supplemented with probiotics and group T3 was supplemented with multienzymes. There was significant (P
Keywords: probiotics; multienzymes; Japanese quails